(untitled) (Jurnal Adabiya, 2020)
This study was aimed at examining the use of swear word in the movies with different topics and characters. The objectives if this study were to find out the reasons of using swear word in the movies. This study was conducted by descriptive qualitative method. The source of data was transcript the movies. The data were identified, analyzed, and categorized based on L,jung ( 2012 ) theory. The technique of data collection was interactive model by Miles and Huberman ( 2014 ). The findings of the study showed that : 1. There are three ways of using swear words such as (1) interjection, (2) emphasizer, (3), expletive slot filler in each movies, but from all of that ways interjections is the most in each movies. 2. The reasons for using the swear words in the movies are psychological; and social movies.